Is overconfidence an individual difference? - Sophia Li; Randall Hale; Don A. Moore (Judgment and Decision Making)
Some scholars have treated overconfidence as an individual difference—that is, assuming the tendency to be overconfident is stable within a person and differs meaningfully from person to person. We question this assumption. We investigate consistency within individuals between its three forms—overestimation, overplacement, and overprecision—in multiple domains (Study 1a and 1b), at multiple times (Study 1b and 2), and with multiple measures (Study 3a and 3b). We find mixed evidence of trait-like consistency. We do find some evidence of within-individual stability across domains and time points. However, we find little consistency across different measures of the same form of overconfidence—specifically overprecision. Instead, we find more consistent evidence that overconfidence varies situationally and contextually.